2018
DOI: 10.11118/actaun201866030737
|View full text |Cite
|
Sign up to set email alerts
|

Technology Acceptance as a Determinant of Online Grocery Shopping Adoption

Abstract: Online grocery shopping plays an important role in the current online market as the most evolving online shopping category. Despite that, consumers adopt this way of shopping quite differently across European countries. To explain such a difference, the Technology acceptance model (TAM) can be used for better understanding consumer behaviour toward habitual online shopping. This paper goes beyond and applies TAM in online grocery area based on the assumption that customers view online grocery shopping as an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 34 publications
(45 reference statements)
3
41
0
1
Order By: Relevance
“…Many studies in the context of online shopping have drawn on the TAM [25,26,27]. Gefen et al [26] suggest that a website is an information technology; hence, the TAM should be viable to explain consumer intention to purchase online.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies in the context of online shopping have drawn on the TAM [25,26,27]. Gefen et al [26] suggest that a website is an information technology; hence, the TAM should be viable to explain consumer intention to purchase online.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Empirical research on online shopping has found that that PEOU exerts a positive impact on PU in both developed and emerging markets [26,36,37]. That is, the easier it is for consumers to use internet connected devices or websites for purchasing products online, the more useful online shopping is perceived to be by these consumers [13,17,25,35,38]. A survey of online grocery shoppers conducted by Kurnia and Chien [39] reveals that the relationship between PEOU and PU is significant and positive.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Online availability in e-shops was slightly preferred and mobile -slightly unpreferred, which was surprising. All the studies and other research papers (Bauerová and Klepek, 2018;Statista, 2019) pointed to consumers preferring online and mobile availability. However, Czechs, although being record online shoppers (Statcounter, 2019), do not prefer shopping online for food products (Špačková, 2018).…”
Section: Discussion Of the Resultsmentioning
confidence: 88%
“…Consumers want to purchase regional products in supermarkets, 59.6% of positive answers and an average of 2.3, and on the internet, 54.5% of positive answers and an average of 2.4. Our colleagues Bauerová and Klepek (2018) argue, that the requirement of online shopping can be explained through Technology Acceptance. The last block of question 17-19 is focused on purchasing behaviour connected with availability.…”
Section: General Presentation Of Research Resultsmentioning
confidence: 99%